2008
DOI: 10.2190/ag.66.2.c
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Residential Mobility in Later Life: Post-Move Perspectives of Elders and Family Members

Abstract: This qualitative study delineates motives for residential mobility, describes dynamics between the elder and family members during the move decision process, and locates the move decision within ecological layers of the aging context. Interviews were conducted with 30 individuals and couples (ages 60-87) who experienced a community-based move within the past year, and with 14 extended family members. Reasons for moving (from perspectives of both elders who moved and their family members) were grouped into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 30 publications
6
62
0
Order By: Relevance
“…A move in old age is considered to be a major life event (Sergeant and Ekerdt 2008), and relocation among old and very old people is a hot topic in the public debate across Europe. Still, the knowledge on factors that predict moves to ordinary housing or to institutional settings is insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A move in old age is considered to be a major life event (Sergeant and Ekerdt 2008), and relocation among old and very old people is a hot topic in the public debate across Europe. Still, the knowledge on factors that predict moves to ordinary housing or to institutional settings is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding relocation to ordinary housing in old age, previous research has identified a diversity of influential aspects. That is, older people do not move because of one but many reasons, with aspects of housing and health highly intertwined (Sergeant and Ekerdt 2008;Stimson and McCrea 2004). A retrospective study among people aged 60-89 who were living alone showed that moves made to another ordinary dwelling were more often motivated by aspects of housing than aspects of health (Oswald et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-and long-distance moves tend to be motivated by different factors and undertaken by different people. For instance, there is a substantial body of work on residential mobility across the life-course that shows that moves are frequently associated with triggers related to life events, such as entry into the labour market, marriage, pregnancy, retirement, and widowhood (Clark and Withers 1999;Sergeant and Ekerdt 2008). Many such "life-course" moves are short-distance, as people upgrade or downgrade their living space, move between city and suburb, or relocate to be closer to place of work.…”
Section: Residential Mobility -Who Moves and Why?mentioning
confidence: 99%
“…Gerontological research suggests that individual-level variables and life course events influence the likelihood of moving in later life. For instance, research has shown that residential mobility in older age is more prevalent among retirees than those still employed, in younger than older old age, among those with higher levels of education or economic resources, in those with health concerns or disability, and those in urban versus rural areas (Sergeant & Ekerdt, 2008;Taylor, Morin, Cohn, & Wang, 2008;Walters, 2002). Less is known about the influence of neighborhood conditions on residential mobility in later life.…”
Section: Introductionmentioning
confidence: 99%